The Conditions Environmental Sanitation, 3M Behavior, and The House Indexwith The Event Of Dengue Dengue Fever (DHF) - Fadhlan Amir Lubis; Putra Apriadi Siregar; Salamudin Salamudin (International Archives of Medical Sciences and Public Health, 2021)
Up to now, the case of DHF is still a health problem in Indonesia, in North Sumatra Province the incidence DHF is still high, and in Pematangsiantar city the incidence DHFis still a health problem. The purpose of this study was to determine the relationship between environmental sanitation, 3M behavior, and the House Index with the incidence ofDHFin the Work Area of the Bah Kapul Health Center, Pematang Siantar City. This study uses a case control approach. This research was conducted in the working area of the Bah Kapul Health Center, Pematang Siantar City during January 2021 to August 2021. The population of this study was patients withDHFwith a sample of 40 cases and a total of 80 control samples. The total sample was 120. The data analysis was univariate analysis. The results showed that the respondents who had good water reservoirs were 110 (91.7%) and respondents who had bad water reservoirs were 10 (8.3%), respondents who had good waste management facilities were 48 (40%) and respondents who have bad waste management sites are 72 (60%), respondents who have good 3M behavior are 78 (64.2%) and respondents who have bad 3M behavior are 42 (35.8%), and respondents who have bad 3M behavior positive larvae were 32 (26.7%) of respondents who were not positive for larvae were 88 (73.3%).